Looking for the Phase Transition—Recent NA61/SHINE Results - Ludwik Turko (Universe, 2018)
The fixed-target NA61/SHINE experiment at the CERN Super Proton Synchrotron (SPS) seeks to find the critical point (CR) of strongly interacting matter as well as the properties of the onset of deconfinement. The experiment provides a scan of measurements of particle spectra and fluctuations in proton–proton, proton–nucleus, and nucleus–nucleus interactions as functions of collision energy and system size, corresponding to a two-dimensional phase diagram (T- μ B ). New NA61/SHINE results are shown here, including transverse momentum and multiplicity fluctuations in Ar+Sc collisions as compared to NA61 p+p and Be+Be data, as well earlier NA49 A+A results. Recently, a preliminary effect of change in the system size dependence, labelled as the “percolation threshold” or the “onset of fireball”, was observed in NA61/SHINE data. This effect is closely related to the vicinity of the hadronic phase space transition region and will be discussed in the text.